Effectiveness of Oral hygiene with Chlorhexidine in the Prevention of VAP: Literature Review - Pongoh, Senny; Makiyah, Sri Nabawiyati Nurul (Universitas Aisyah Pringsewu, 2022)
Background: Ventilator Assisted Pneumonia (VAP) is the most well-known nosocomial disease that occurs 48 hours after a patient is intubated on a ventilator in the ICU. The incidence of VAP can increase the length of stay of patients in the ICU, increasing patient morbidity and mortality. One of the efforts to prevent VAP is to perform oral hygiene. Objective: to determine the effectiveness of chlorhexidine in oral hygiene on the prevention of VAP. Methods: The method consists of five stages, namely, identifying questions, identifying relevant articles using the Google Schoolar, PubMed, and Scopus databases with keywords. The selection of articles using PRISMA Flowchart and data extraction compiled, summarized and reported the results. The inclusion criteria were articles related to the effectiveness of chlorhexidine, lactoperixidase with the occurrence of VAP, articles published from 2010 to 2021, full text articles in English and Indonesian, the patient population was patients on ventilators. Results: Of the 55 articles relevant to the title and abstract, 6 articles met the inclusion criteria. Where 0.2% chlorhexidine is more effective in reducing the risk of VAP. Although chlorhexidine 0.2% is more effective than lactoperoxidase, other agents can be used in the field to prevent VAP. Conclusion: It was concluded from the six existing articles that 0.2% chlorhexidine was more effective in reducing the risk of VAP, to prevent infection other alternatives could be used, namely 0.1% chlorhexidine, Echinacea ingredients, lactoperoxidase solution and listerin. Abstrak: Latar Belakang: Ventilator Assisted Pneumonia (VAP) merupakan penyakit nosokomial paling terkenal yang terjadi 48 jam setelah pasien diintubasi pada ventilator di ICU. Kejadian VAP dapat meningkatkan lama rawat pasien di ICU, meningkatkan morbiditas dan mortalitas pasien. Salah satu upaya pencegahan VAP adalah dengan melakukan oral hygiene. Tujuan: untuk mengetahui efektivitas klorheksidin dalam kebersihan mulut dalam pencegahan VAP. Metode: Desain tinjauan pustaka dengan artikel yang relevan menggunakan database Google Schoolar, PubMed, dan Scopus. Kriteria inklusi adalah artikel terkait efektivitas klorheksidin, laktoperiksidase dengan terjadinya VAP, artikel terbitan 2010 sd 2021, artikel full text dalam bahasa Inggris dan Indonesia, populasi pasien adalah pasien yang menggunakan ventilator. Hasil: Enam artikel digunakan dalam review. Dimana klorheksidin 0,2% lebih efektif dalam menurunkan risiko VAP. Meskipun klorheksidin 0,2% lebih efektif daripada laktoperoksidase, agen lain dapat digunakan di lapangan untuk mencegah VAP. Untuk mencegah infeksi dapat digunakan alternatif lain yaitu klorheksidin 0,1%, bahan Echinacea, larutan laktoperoksidase dan listerin. Kesimpulan: Klorheksidin 0,2% lebih efektif dalam menurunkan risiko VAP.